1982
DOI: 10.1111/j.1471-0528.1982.tb04678.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of complete bed rest versus ambulation in the management of proteinuric hypertension during pregnancy

Abstract: Summary. Forty patients participated in a randomized controlled trial of complete bed rest versus ambulation as desired in the management of proteinuric hypertension during pregnancy. Daily increases in serum human placental lactogen and oestriol concentrations were greater in the rested group. An especially‘at risk’ group of 10 patients with both hyperuricaemia and severe fetal growth retardation was identified. Strict confinement to bed in these cases seemed to encourage the development of the premonitory s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…Based on the increased suspicion of pregnancy‐induced hypertension, the clinician could implement more frequent (ie, weekly) prenatal visits, encourage more frequent rest periods (ie, two or three half‐hour periods daily), instruct the client in relaxation techniques, and reassess the adolescent's dietary protein intake 18–20 . The efficacy of these measures to prevent PIH still is uncertain, 21,22 and their potential usefulness is based on early recognition of the gravida at increased risk 23 . The use of the MAP along with factors in the adolescent's social and family background permits the implementation of these additional measures.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the increased suspicion of pregnancy‐induced hypertension, the clinician could implement more frequent (ie, weekly) prenatal visits, encourage more frequent rest periods (ie, two or three half‐hour periods daily), instruct the client in relaxation techniques, and reassess the adolescent's dietary protein intake 18–20 . The efficacy of these measures to prevent PIH still is uncertain, 21,22 and their potential usefulness is based on early recognition of the gravida at increased risk 23 . The use of the MAP along with factors in the adolescent's social and family background permits the implementation of these additional measures.…”
Section: Discussionmentioning
confidence: 99%
“…Definitions have varied widely, compliance questioned [279], and RCT data are limited. For preeclampsia, strict (vs. some) bed rest in hospital does not alter outcomes [297]. For gestational hypertension, some bed rest in hospital (vs. routine activity at home) decreases severe hypertension (RR 0.58; 95% CI 0.38-0.89) and preterm birth (RR 0.53; 95% CI 0.29-0.99), although women prefer unrestricted activity at home [296]; whether benefits are from bed rest or hospitalization is not clear.…”
Section: Commentsmentioning
confidence: 99%
“…Thromboprophylaxis use should be based on number of thromboembolic risk markers, especially preeclampsia associated with adverse perinatal outcome, advanced maternal age, obesity, prolonged antenatal bed rest, postpartum haemorrhage, and emergency Caesarean delivery [297,486,487]. The duration of thromboprophylaxis may vary from until full mobilization to 4-6 weeks postpartum (also, see 'Anaesthesia').…”
Section: Commentsmentioning
confidence: 99%
“…There is little evidence of efficacy in improving these pregnancy outcomes, and prescribed bed rest involves substantial emotional, physical and financial costs. 2,3 Few randomized trials have been conducted; these have not shown a beneficial effect of bed rest for threatened miscarriage, 4 hypertension 5,6 or fetal growth retardation. 7 The significantly increased ultradistal bone loss associated with bed rest in this study underscores the need for further evaluation of this treatment for specific pregnancy 8 complications.…”
Section: Discussionmentioning
confidence: 99%